Full Aeroelastic Model Testing for Examining Wind-Induced Vibration of a 5,000 m Spanned Suspension Bridge - Ge, Yaojun; Xia, Jinlin; Zhao, Lin; Zhao, Shiyu (Frontiers in Built Environment, 2018)
This paper presents an experimental investigation on wind-induced vibrations of a suspension bridge with ultimate main span length, including flutter and buffeting. Since the upper limit of a suspension bridge’s main span can reach more than 5,000m based on strength and weight of steel main cables, a feasible prototype with a span arrangement of 2,000m+5,000m +2,000m has been proposed. In order to improve flutter stability, a twin box girder has been designed with a 40m slot in center and two 20m wide decks suspended by four main cables. Its full aeroelastic model was designed and manufactured with the geometrical scale of 1:620, and the wind tunnel testing was carried out under smooth flows and turbulent flows for different angles of attack. A big difference in critical flutter speed was found between the proposed slotted girder and corresponding slot-sealed girder, which verifies the necessity of a widely-slotted twin box girder for a super-long suspension bridge. Among three angles of attack, the critical flutter speed under smooth flow has the maximum value of 80.9 m/s at -3° and the minimum value of 51.4m/s at 3°. On-coming turbulence will not only cause buffeting responses but also influence the critical flutter speed in an unfavorable way.